The effects of ibudilast, a glial activation inhibitor, on opioid withdrawal symptoms in opioid‐dependent volunteers. (14th May 2015) - Cooper, Ziva D.; Johnson, Kirk W.; Pavlicova, Martina; Glass, Andrew; Vosburg, Suzanne K.; Sullivan, Maria A.; Manubay, Jeanne M.; Martinez, Diana M.; Jones, Jermaine D.; Saccone, Phillip A.; Comer, Sandra D.
Abstract: Glial activation is hypothesized to contribute directly to opioid withdrawal. This study investigated the dose‐dependent effects of a glial cell modulator, ibudilast, on withdrawal symptoms in opioid‐dependent volunteers after abrupt discontinuation of morphine administration. Non‐treatment‐seeking heroin‐dependent volunteers ( n  = 31) completed the in‐patient, double‐blind, placebo‐controlled, within‐subject and between‐group study. Volunteers were maintained on morphine (30 mg, QID) for 14 days and placebo (0 mg, QID) for the last 7 days of the 3‐week study. Volunteers also received placebo (0 mg, PO, BID) capsules on days 1–7. On days 8–21, volunteers were randomized to receive ibudilast (20 or 40 mg, PO, BID) or placebo capsules. Subjective and clinical ratings of withdrawal symptoms were completed daily using daily using the Subjective Opioid Withdrawal Scale (SOWS) and Clinical Opioid Withdrawal Scale (COWS). Medication side effects were also monitored. Relative to the first 2 weeks, all groups exhibited withdrawal during the third week as assessed by the SOWS and COWS ( P  ≤ 0.0001). Although overall SOWS scores did not differ between groups, exploratory analyses pooling the two ibudilast groups demonstrated that they had lower ratings of withdrawal symptoms on SOWS items ('anxious, ' 'perspiring, ' 'restless, ' 'stomach cramps') during detoxification relative to the placebo group. Ibudilast was well tolerated; no serious adverse events occurred during the study. Pharmacological modulation of glial activity with ibudilast decreased some subjective ratings of opioid withdrawal symptoms. These exploratory findings are the first to demonstrate the potential clinical utility of glial modulators for treating opioid withdrawal in humans. Abstract : Glial activation is hypothesized to contribute directly to opioid withdrawal symptoms. This inpatient, double‐blind, placebo‐controlled, between‐groups study investigated the effects of a glial cell‐modulator, ibudilast, on withdrawal symptoms in opioid‐dependent volunteers after abrupt discontinuation of morphine administration. Volunteers receiving ibudilast (20 or 40 mg, PO, BID) reported lower subjective ratings of withdrawal symptoms ('Anxious, ' 'Perspiring, ' 'Restless, ' 'Stomach Cramps') relative to the placebo group. These findings demonstrate the potential clinical utility of glial modulators for treating opioid withdrawal symptoms in humans.